ANALISIS STRUKTUR DAN BUDAYA PESANTREN PADA NOVEL BIDADARI BERMATA BENING KARYA HABIBURRAHMAN EL SHIRAZY - Solihat, Ai; Sahidin, Didin; Nurwahidah, Lina Siti; Naida, Winka (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This research is entitled "Structure and Culture Analysis of Islamic Boarding Schools in Habiburrahman El Shirazy's Novel Bidadari Bermata Bening". This research was carried out due to the good things in the novel which should be used as examples, role models, and learning media for students to improve character (character) according to what is contained in the 2013 curriculum. The research method used was a qualitative descriptive method. The object of this study is the novel Bidadari Bermata Bening by Habiburrahman El Shirazy. The results of the research show that the novel Bidadari Bermata Bening has a logical and chronological storytelling structure. The theme raised in the story is the culture of the pesantren. The background taken is the location of the Islamic boarding school with figures who uphold the culture of the Islamic boarding school. Islamic boarding school culture which is characteristic of Islamic boarding schools includes several aspects, namely boarding, piety, humility, and fortitude.